A glass fiber reinforced pa66 / sps composition, its preparation method and application

CN122483564BActive Publication Date: 2026-10-27SHANGHAI KINGFA SCI & TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610942271.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-27
Estimated Expiration
2046-06-29

AI Technical Summary

Technical Problem

另一方面,sPS树脂较高的结晶度也赋予其较好的气体阻隔性,但关于PA66/sPS合金产品的气体阻隔性研究较少

Benefits of technology

本发明通过在玻纤增强PA66体系中引入间规聚苯乙烯(sPS)树脂,同时通过不同类型的结晶调控剂的复配,制备得到的玻纤增强PA66/sPS组合物兼具较好的高温下尺寸稳定性以及很好的水蒸气阻隔性,在连接器、家电等领域有较好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a glass fiber reinforced PA66 / sPS composition and a preparation method and application thereof, and comprises the following components: PA66 resin 30-60 parts, syndiotactic polystyrene 15-30 parts, glass fiber 10-30 parts, compatilizer 2-8 parts, and crystallization regulator 0.1-2 parts. The glass fiber reinforced PA66 / sPS composition prepared by introducing the syndiotactic polystyrene (sPS) resin into the glass fiber reinforced PA66 system and by compounding different types of crystallization regulators has good size stability at high temperature and good water vapor barrier property, and has a good application prospect in the fields of connectors and household appliances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of engineering plastics technology, specifically relating to a glass fiber reinforced PA66 / sPS composition, its preparation method, and its application. Background Technology

[0002] Syntactic polystyrene (sPS) resin possesses excellent properties such as good heat resistance, low density, good chemical resistance, and low dielectric loss, making it widely used in connectors, radar covers, kitchen appliances, and other fields. However, pure sPS resin has a relatively rigid molecular chain and is quite brittle, making it difficult to use alone. PA66 / sPS alloys offer a more balanced mechanical property and are also widely used.

[0003] However, in practical use, it was found that PA66 / sPS alloy parts undergo dimensional changes and significant shrinkage during subsequent high-temperature applications. This is because the sPS resin molecular chain contains a large number of benzene rings, resulting in significant steric hindrance during crystallization. The crystals cannot align properly during cooling, leading to cold crystallization at higher temperatures. On the other hand, the high crystallinity of sPS resin also imparts good gas barrier properties, but research on the gas barrier properties of PA66 / sPS alloy products is limited.

[0004] Therefore, there is an urgent need to develop a glass fiber reinforced PA66 / sPS composition that has both good dimensional stability at high temperatures and water vapor barrier properties. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, the present invention aims to provide a glass fiber reinforced PA66 / sPS composition that has both good dimensional stability at high temperatures and water vapor barrier properties.

[0006] This invention is achieved through the following technical solution: A glass fiber reinforced PA66 / sPS composition, comprising the following components by weight: 30-60 parts of PA66 resin 15-30 parts of syndiotactic polystyrene 10-30 parts glass fiber 2-8 parts compatibilizer Crystallization regulator 0.2-2 parts Wherein, the crystallization regulator is a compound of crystallization regulator 1 and crystallization regulator 2 in a mass ratio of (0.5-2):1; The crystallization regulator 1 is one or more of talc, calcium carbonate, silicon dioxide or titanium dioxide; The crystallization regulator 2 is one or more of benzenesulfonamide compounds, polyvinylpyrrolidone, or calcium chloride.

[0007] Preferably, the benzenesulfonamide compound is selected from one or more of N-butylbenzenesulfonamide, N-ethyl-p-toluenesulfonamide, or N-methyl-p-toluenesulfonamide.

[0008] This invention introduces syndiotactic polystyrene (sPS) resin into the glass fiber reinforced PA66 system, and through the compounding of different types of crystallization regulators, can significantly improve the high-temperature dimensional stability of injection-molded products of glass fiber reinforced PA66 / sPS alloy system, while also greatly improving the water vapor barrier properties of the system.

[0009] In the glass fiber reinforced PA66 / sPS composition of the present invention, the mass percentage of PA66 resin is not less than 25%.

[0010] Preferably, the relative viscosity of the PA66 resin is 2.0-2.8 (for example, it can be 2.0, 2.2, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or any range between the above values), and the relative viscosity is tested according to the ISO 307:2019 test standard at a test temperature of 23°C.

[0011] In the glass fiber reinforced PA66 / sPS composition of the present invention, the mass percentage of syndiotactic polystyrene is 13%-32% (for example, it can be 13%, 15%, 17%, 18%, 20%, 22%, 25%, 27%, 29%, 30%, 32% or any range between the above proportions).

[0012] The syndiotactic polystyrene resin described in this invention can be obtained from commercial sources or can be prepared in-house. The preparation method is based on CN112646066B.

[0013] The syndiotactic polystyrene described in this invention has a weight-average molecular weight of 70,000-240,000 g / mol. The testing method is as follows: a high-temperature gel permeation chromatography system (GPC-IR, Polymer Char, Spain, equipped with dual infrared and viscosity detectors) was used, with 1,2,4-trichlorobenzene as the mobile phase, a flow rate of 1.0 mL / min, a column temperature of 160℃, a detector temperature of 160℃, and an injector temperature of 160℃. A calibration curve was established using polystyrene standards (weight-average molecular weight range: 266-12,900,000 g / mol). The sample was dissolved in trichlorobenzene (concentration 0.125 mg / mL), and the injection volume was 200 μL. Data were processed using GPC ONE software to obtain the weight-average molecular weight (Mw).

[0014] Preferably, the mass ratio of syndiotactic polystyrene to PA66 resin is 1:(1-4), (for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any range between the above ratios), preferably 1:(1.5-3.5). This invention introduces syndiotactic polystyrene resin into the glass fiber reinforced PA66 system and controls the mass ratio of syndiotactic polystyrene to PA66 resin within this range, which can improve the high-temperature dimensional stability and water vapor barrier properties of injection-molded products of the glass fiber reinforced PA66 / sPS alloy system.

[0015] In the glass fiber reinforced PA66 / sPS composition of the present invention, the mass percentage of the crystallization regulator is 0.15%-2.2% (for example, it can be 0.2%, 0.25%, 0.3%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.1%, 2.2% or any range between the above proportions).

[0016] The mass ratio of crystallization regulator 1 to crystallization regulator 2 in this invention is (0.5-2):1 (for example, it can be 0.5:1, 0.8:1, 1:1, 1.25:1, 1.5:1, 2:1, or any range between the above values). By controlling the compounding ratio of specific crystallization regulators within this range, this invention enables the material to simultaneously possess both excellent high-temperature dimensional stability and water vapor barrier properties.

[0017] In a further preferred embodiment of the present invention, the crystallization regulator 1 is talc powder and the crystallization regulator 2 is polyvinylpyrrolidone.

[0018] The polyvinylpyrrolidone of the present invention has a viscosity-average molecular weight of 8,000-700,000 and a degree of polymerization K value between 82 and 95.

[0019] Preferably, the compatibilizer is maleic anhydride-grafted polyphenylene ether resin. More preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether resin is between 0.2% and 1.5% (for example, it can be 0.2%, 0.4%, 0.5%, 0.7%, 0.8%, 0.9%, 1.0%, 1.2%, 1.4%, 1.5% or any of the above proportions).

[0020] The maleic anhydride-grafted polyphenylene ether resin of the present invention can be obtained commercially or by self-production. The self-production method can be as follows: PPE resin, maleic anhydride and initiator are added to a twin-screw extruder in proportion and mixed at 260~280°C to obtain maleic anhydride-grafted polyphenylene ether resins with different grafting rates.

[0021] The initiator is at least one of 1,4-di-tert-butylperoxyisopropylbenzene, diisopropylbenzene peroxide, benzoyl peroxide, and di-tert-butyl peroxide.

[0022] The maleic anhydride grafting rate test method for the maleic anhydride-grafted polyphenylene ether resin (MAH-g-PPE) adopts the acid-base titration method. Specifically, acetone is used as a solvent to remove unreacted maleic anhydride from MAH-g-PPE by Soxhlet extraction. Then, MAH-g-PPE is dissolved in an organic solvent (such as xylene). Then, an excess of strong base (such as sodium hydroxide) is added to hydrolyze the anhydride groups. Then, the unreacted strong base is back-titrated with a strong acid (such as hydrochloric acid). Finally, the maleic anhydride grafting rate of MAH-g-PPE is calculated based on the titration results.

[0023] Preferably, the glass fiber is alkali-free chopped glass fiber, and more preferably, hydrolysis-resistant alkali-free chopped glass fiber.

[0024] As a further preferred embodiment of the present invention, the glass fiber is a hydrolysis-resistant, alkali-free short-cut glass fiber with a chopped length of 3-4.5 mm and a fiber diameter of 9-13 mm.

[0025] According to actual performance requirements, the glass fiber reinforced PA66 / sPS composition of the present invention further includes 0-3 parts by weight of processing aids, wherein the processing aids include at least one of lubricant and antioxidant.

[0026] Preferably, the antioxidant is at least one of hindered phenols or hindered amines.

[0027] For example, the antioxidants include, but are not limited to, antioxidant 1098, antioxidant 1010, antioxidant 1076, antioxidant 245, antioxidant 168, etc.

[0028] Preferably, the lubricant is one or more of silicone, ethylene-acrylic acid copolymer wax, or sodium lignite, and more preferably a mixture of ethylene-acrylic acid copolymer wax and sodium lignite.

[0029] The present invention also provides a method for preparing the above-mentioned glass fiber reinforced PA66 / sPS composition, comprising the following steps: According to the formula, except for the glass fiber side feed, all components are mixed evenly and fed to the main feeder. After melt blending, they are extruded and granulated to obtain the glass fiber reinforced PA66 / sPS composition.

[0030] Preferably, the melt blending is carried out in a twin-screw extruder with a length-to-diameter ratio of 36 to 48:1 (e.g., 36:1, 38:1, 40:1, 42:1, 45:1, 48:1 or any range thereof), a screw speed of 300 to 500 rpm (e.g., 300 rpm, 320 rpm, 350 rpm, 400 rpm, 430 rpm, 460 rpm, 500 rpm or any value between these ranges), and an extrusion temperature of 270 to 290°C (e.g., 270°C, 275°C, 280°C, 285°C, 290°C or any value between these ranges).

[0031] The present invention also provides a connector comprising the above-described glass fiber reinforced PA66 / sPS composition.

[0032] Compared with the prior art, the present invention has the following beneficial effects: This invention introduces syndiotactic polystyrene (sPS) resin into a glass fiber reinforced PA66 system, and through the compounding of different types of crystallization regulators, prepares a glass fiber reinforced PA66 / sPS composition that has both good dimensional stability at high temperatures and excellent water vapor barrier properties, and has good application prospects in connectors, home appliances and other fields. Detailed Implementation

[0033] The present invention will be further illustrated below through specific embodiments. The following embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following embodiments.

[0034] Unless otherwise specified, all materials used in this invention can be purchased commercially or prepared using conventional methods.

[0035] The raw materials used in this invention are sourced from the following sources: PA66-1 resin: PA66 EPR24, relative viscosity 2.4, Shenma Group; PA66-2 resin: PA66 EPR27, relative viscosity 2.7, Shenma Group; sPS-1 resin: weight average molecular weight 1.66 × 10⁻⁶ 5g / mol, self-made: At a polymerization temperature of 70℃, 3.8L of toluene, 10.0L of styrene, 9L of methylaluminoxane-toluene solution (containing 15 mol of methylaluminoxane), and 2L of pentamethylcyclopentadienyl-(3-methyl-4-quinolinoxy)-dimethoxytitanium / toluene solution (containing 10 mmol of catalyst) were added sequentially, and the timer was started. After 2 hours of polymerization, the reaction solution was carefully poured into the reactor, acidified ethanol was added, and the mixture was stirred thoroughly. The polymer was obtained by filtration, and the filter cake was dried under vacuum and weighed. The polymer was then refluxed in boiling acetone for 2 hours, filtered while hot, and a solid polymer was obtained. The solid polymer was then dried under vacuum to obtain sPS-1 resin. sPS-2 resin: weight average molecular weight 0.72×10 5 g / mol, self-made: At a polymerization temperature of 55℃, 3.8 L of toluene, 10.0 L of styrene, 9 L of methylaluminoxane-toluene solution (containing 15 mol of methylaluminoxane), and 2 L of pentamethylcyclopentadienyl-4-quinolinoxy-dimethoxytitanium / toluene solution (containing 10 mmol of catalyst) were added sequentially, and the timer was started. After 2 hours of polymerization, the reaction solution was carefully poured into a reactor, acidified ethanol was added, and the mixture was stirred thoroughly. The polymer was obtained by filtration, and the filter cake was vacuum dried and weighed. The polymer was then refluxed in boiling acetone for 2 hours, filtered while hot, and a solid polymer was obtained. This solid polymer was then vacuum dried to obtain sPS-2. Talc: HTP Ultra 5L, particle size D50 is 0.65mm, Liaoning Aihai; Calcium carbonate: AC-05N, with a particle size D50 of 3.5mm after screening, manufactured by Guangdong Xianglong Technology. Polyvinylpyrrolidone: PVPK-90, viscosity-average molecular weight 350,000, K value 85, Shanghai Kema; N-Butylbenzenesulfonamide: JZ-218: Suzhou Jinzhong Chemical Co., Ltd. Compatibilizer: Maleic anhydride-grafted polyphenylene ether resin, maleic anhydride grafting rate 0.5wt%, self-made; The method for preparing maleic anhydride-grafted polyphenylene ether resin involves adding polyphenylene ether resin, commercially available maleic anhydride, and initiator 1,4-di-tert-butylperoxyisopropylbenzene into a twin-screw extruder, and controlling the mass ratio of maleic anhydride, polyphenylene ether, and initiator to 0.6:99.1:0.3 for mixing. This yields maleic anhydride-grafted polyphenylene ether resin with a grafting rate of 0.5%. The extrusion temperatures of zones 1 to 10 of the twin-screw extruder are 260℃, 260℃, 270℃, 280℃, 250℃, 250℃, 250℃, 250℃, 260℃, and 280℃, respectively. Fiberglass: ECS10-03-568H, Jushi Group; Antioxidant: RIANOX 1098; Lubricant: HG540, ethylene-acrylic acid copolymer wax, Jiangxi Weike.

[0036] Lubricant: Sodium lignite, LICOMONT NAV101 PWD, Clariant Group; Preparation methods for the examples and comparative examples: According to the proportions in Tables 1 and 2, except for the glass fiber side feed, all components were mixed evenly and fed to the main feeder. The mixture was then extruded and granulated using a twin-screw extruder to obtain the glass fiber reinforced PA66 / sPS composition. The twin-screw extruder had an aspect ratio of 42:1, a screw speed of 400 rpm, and an extrusion temperature of 270~290℃.

[0037] Performance testing methods: Post-shrinkage percentage: The particles of the glass fiber reinforced PA66 / sPS composition were dried in an oven at 120℃ for 4 hours, and then a 200*50*2mm shrinkage plate was injection molded using the same injection molding process. The measurement direction was transverse to evaluate the dimensional stability during high-temperature baking. After the injection-molded shrinkage plate was placed at room temperature, the initial dimension L0 was measured. Then it was placed in an oven at 150℃ for 2 hours, removed and cooled to room temperature, and the dimension L1 was measured. The post-shrinkage percentage m was calculated as (L1-L0) / L0×100%.

[0038] Water vapor transmission rate: The particles of the glass fiber reinforced PA66 / sPS composition were injection molded into 100*100*1.0mm square plates. The water vapor transmission rate of the square plate material was tested using a water vapor transmission rate tester. The water vapor transmission rate of the material was tested using the humidity sensor method according to GB / T 30412 2013 standard.

[0039] Table 1. Components (parts by weight) and test results in Examples 1-10

[0040] Table 2. Components (parts by weight) and test results in Comparative Examples 1-8

[0041] Compared with Example 1, in Comparative Examples 1-2, the mass ratio of PA66 to sPS resin is not within the scope of this invention, and the resulting composition cannot have both good dimensional stability at high temperature and water vapor barrier properties.

[0042] In Comparative Examples 3-4, the compositions prepared using a single crystallization regulator exhibited poor dimensional stability and water vapor barrier properties at high temperatures.

[0043] In Comparative Examples 5-6, the mass ratio of crystallization regulator 1 to crystallization regulator 2 was outside the range, and the resulting compositions had poor dimensional stability and water vapor barrier properties at high temperatures.

[0044] In Comparative Examples 7-8, the sum of the amounts of crystallization regulator 1 and crystallization regulator 2 was outside the range. When the amount was small, the dimensional stability and water vapor barrier properties were poor. When the amount was large, the resulting composition had a low shrinkage rate but poor water vapor permeability.

Claims

1. A glass fiber reinforced PA66 / sPS composition, characterized in that, By weight, it includes the following components: 30-60 parts of PA66 resin 15-30 parts of syndiotactic polystyrene 10-30 parts glass fiber 2-8 parts compatibilizer Crystallization regulator 0.2-1.5 parts Wherein, the crystallization regulator is a compound of crystallization regulator 1 and crystallization regulator 2 in a mass ratio of (0.5-2):1; The crystallization regulator 1 is talc powder; The crystallization regulator 2 is polyvinylpyrrolidone.

2. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The mass ratio of the syndiotactic polystyrene to PA66 resin is 1:(1-4).

3. The glass fiber reinforced PA66 / sPS composition according to claim 2, characterized in that, The mass ratio of syndiotactic polystyrene to PA66 resin is 1:(1.5-3.5).

4. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The weight-average molecular weight of the syndiotactic polystyrene is 70,000-240,000 g / mol.

5. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The relative viscosity of the PA66 resin is 2.0-2.8, and the test temperature is 23℃ according to ISO 307 test standard.

6. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The compatibilizer is maleic anhydride-grafted polyphenylene ether resin.

7. The glass fiber reinforced PA66 / sPS composition according to claim 6, characterized in that, The maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether resin is between 0.2% and 1.5%.

8. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The glass fiber is alkali-free short-cut glass fiber.

9. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The glass fiber is a hydrolysis-resistant, alkali-free chopped glass fiber.

10. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The glass fiber is a hydrolysis-resistant, alkali-free short-cut glass fiber with a chopped length of 3-4.5 mm and a fiber diameter of 9-13 micrometers.

11. The glass fiber reinforced PA66 / sPS composition according to claim 1, characterized in that, The product also includes 0-3 parts by weight of processing aids, which include at least one of lubricant and antioxidant.

12. A method for preparing the glass fiber reinforced PA66 / sPS composition according to any one of claims 1-11, characterized in that, The process includes the following steps: according to the formula, except for the glass fiber side feed, the components are mixed evenly and fed to the main feed, melt-blended and then extruded and granulated to obtain the glass fiber reinforced PA66 / sPS composition.

13. A connector comprising the glass fiber reinforced PA66 / sPS composition according to any one of claims 1-11.

Citation Information

Patent Citations

  • A catalytic polymerization system and polymerization method for styrene polymerization and the resulting polystyrene

    CN112646066B

  • Semi-aromatic polyamide composite material as well as preparation method and application thereof

    CN116178942A

  • Polyamide molding composition and preparation method thereof

    CN120173405A